Morphological diversity of setae on the second maxilliped of fiddler crabs (Decapoda: Ocypodidae) from the southwestern Atlantic coast - Colpo, Karine Delevati [UNESP]; Negreiros-Fransozo, Maria Lucia [UNESP] (Wiley, 2013)
Fiddler crabs are deposit feeders, and use the setae on their mouth appendages to manipulate sediment particles to extract food. The number of spoon-tipped setae on the second maxilliped is frequently related to the distribution of fiddler crabs on estuarine sediments, but no study has compared the morphological diversity of these setae among multiple fiddler crab species. Here, we describe and classify the setae of the second maxillipeds of the nine Uca spp. known from the Brazilian coast. The second maxilliped of each species was examined by scanning electron microscopy. Six types of setae (five papposerrate, and one pappose) were described on the meropodite of the second maxilliped. Among the papposerrate setae, one type had a spoon-like tip, and the morphology of this type, especially the degree of curvature, differed between species. Members of Uca leptodactylus, U. uruguayensis, and U. maracoani had highly concave spoon-tipped setae. In U. rapax and U. cumulanta, the setal tip was moderately curved, while in U. thayeri, U. burgersi, and U. mordax, this curvature was slight. At the other extreme, the meropodite of the second maxilliped of U. vocator lacked setae altogether. This is the first study that describes differences in the degree of curvature of spoon-tipped setae in fiddler crabs. This trait may be strongly related to the distribution of these fiddler crabs on different estuarine substrates. © 2012, The American Microscopical Society, Inc.
Keywords: Brazil; Scanning electron microscopy; Spoon-tipped setae; Leptodactylus; Ocypodidae; Uca; Uca burgersi; Uca cumulanta; Uca maracoani; Uca rapax; Uca thayeri; Uca uruguayensis; Uca vocator